2020
DOI: 10.1002/mp.14072
|View full text |Cite
|
Sign up to set email alerts
|

A convolutional neural network‐based model observer for breast CT images

Abstract: Purpose: In this paper, we propose a convolutional neural network (CNN)-based efficient model observer for breast computed tomography (CT) images. Methods: We first showed that the CNN-based model observer provided similar detection performance to the ideal observer (IO) for signal-known-exactly and background-known-exactly detection tasks with an uncorrelated Gaussian background noise image. We then demonstrated that a singlelayer CNN without a nonlinear activation function provided similar detection performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…CNNs also have strong representational power to learn non-linear functions, which makes it possible to develop a single model that generalizes to different imaging conditions. It has been shown that CNNs can approximate an ideal model observer [12], [13] and generally perform better than human observers [14] when they are trained with ground truth label (e.g., 1 for all signal-present images and 0 for all signal-absent images). Therefore, to implement CNNbased anthropomorphic model observers, it is necessary to reflect the human inefficiency in CNNs.…”
Section: Introductionmentioning
confidence: 99%
“…CNNs also have strong representational power to learn non-linear functions, which makes it possible to develop a single model that generalizes to different imaging conditions. It has been shown that CNNs can approximate an ideal model observer [12], [13] and generally perform better than human observers [14] when they are trained with ground truth label (e.g., 1 for all signal-present images and 0 for all signal-absent images). Therefore, to implement CNNbased anthropomorphic model observers, it is necessary to reflect the human inefficiency in CNNs.…”
Section: Introductionmentioning
confidence: 99%
“…Data augmentation was used to increase both the size and the diversity of the training data set. Gaussian filters ( 16 ) are used to transform the input image in the data augmentation step. After data augmentation, all images were resized to 512 × 512 pixels, and a mean normalization was performed as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, because we conducted a binary classification task, the network architecture was much more cost‐effective than a VGG network, as it reduced the number of network parameters and training images required. In our previous study, 21 we found that a CNN‐based model observer provided better detection performance than a conventional linear model observer when it was trained using more than 10 000 image pairs. Thus, we implemented the observer loss using Mayo Clinic data, which contained more than 10 000 pairs of image patches.…”
Section: Introductionmentioning
confidence: 93%
“…For all the network architectures in Figure 3, there were no improvements in the detection accuracies when the number of image pairs used for observer network training was more than 10 000 in the SKE detection task, which was consistent with our previous findings. 21 For SKS detection, there were no improvements in the detection accuracies when the number of image pairs used for training was more than 20 000 because this task was more complex than SKE detection. The weights of the convolution layers were initialized to random values sampled from a Gaussian distribution with zero mean and a standard deviation of √ 2∕N, where N is the number of incoming nodes (i.e., He normalization).…”
Section: Training For the Observer Networkmentioning
confidence: 99%